THE POWER OF NETIZEN +62: KONTRUKSI KONFLIK FENOMENAL DI MEDIA SOSIAL - Eka Susilawati; Rizqi Fitrianti; Noerma Kurnia Fajarwati (Universitas Bina Bangsa, 2022)
Unlimited information exchange in the modern era presents a new name for the media user audience, one of which is netizen +62. In Indonesia, the power of netizens +62 cannot be doubted, especially in constructing a growing social reality issue that is shared on social media. This study aims to describe the pros and cons of the existence of netizens +62 studied from the point of view of communication. The study used a qualitative approach with virtual ethnographic methods. This study concludes that netizen +62 has a significant role in influencing the flow of information and interactivity on social media. Netizens +62 in this case are no longer just objects of information exposure, but play an active role in controlling the flow of information that occurs, so that they have the power to build their 'own' construction related to phenomenal conflicts that are shared on social media